The global marketing imperative - Czinkota, Michael (Henry Stewart Talks, 2009)
Trade growth, Key benefits, Changing power of governments, Introduction to new rules of regulation, New rules of competition, Only best in class projects, New meaning of targeting, Focus on process thinking